Evaluation of Inflammatory Markers (CRP, IL-6, TNF-α) in Type 2 Diabetes Mellitus: A Cross-Sectional Study - Muqadas Shabbir (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) is a major global health concern characterized not only by chronic hyperglycemia but also by a state of persistent low-grade systemic inflammation. Inflammatory biomarkers such as C-reactive protein (CRP), Interleukin-6 (IL-6), and Tumor Necrosis Factor-alpha (TNF-α) are increasingly recognized for their role in insulin resistance, endothelial dysfunction, and the development of diabetic complications. Objective: To evaluate the levels of inflammatory markers (CRP, IL-6, TNF-α) in patients with T2DM and to determine their association with glycemic control and clinical parameters. Methods: This cross-sectional study was conducted at the University of Lahore Teaching Hospital from June 2022 to September 2023. A total of 110 participants were enrolled, including 55 T2DM patients and 55 healthy controls. Fasting blood samples were collected to measure CRP, IL-6, TNF-α, fasting blood glucose, and HbA1c. Data were analyzed using SPSS version 26. Independent t-tests and Pearson correlation analysis were applied, with p<0.05 considered statistically significant. Results: T2DM patients exhibited significantly higher levels of CRP (7.18 ± 2.34 mg/L), IL-6 (10.24 ± 3.66 pg/mL), and TNF-α (11.88 ± 4.12 pg/mL) compared to controls (p<0.001). HbA1c showed a strong positive correlation with CRP (r=0.64), IL-6 (r=0.59), and TNF-α (r=0.56). Patients with poor glycemic control had significantly higher inflammatory marker levels than those with better control. Conclusion: Inflammatory markers are significantly elevated in T2DM and are closely associated with poor glycemic control. These biomarkers may serve as useful indicators of disease severity and potential predictors of complications. Keywords: Type 2 Diabetes Mellitus, CRP, IL-6, TNF-α, Inflammation, HbA1c, Biomarkers, Insulin Resistance.